2020
DOI: 10.1007/978-3-030-58805-2_44
|View full text |Cite
|
Sign up to set email alerts
|

Literacy Toy for Enhancement Phonological Awareness: A Longitudinal Study

Abstract: In this report it is presented the results of a longitudinal pre-experimental study, it was realized a technological intervention to stimulate the phonological awareness through a tangible reading toy based on the RFID technology, consisting of a teddy bear and 30 letters in 3D from the Spanish alphabet. This study started with a sample of 200 children, from them, there were selected 17 children aged between 6 and 7 years (Mage = 6.47, SD = .51) with a phonological disorder from an educative institution. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This function is extremely important because if we transfer the emulator to real computing environments, such as work or education, the person with motor disabilities must be able to correctly drag objects using EMKEY. This statement is related to previous research in which technological devices, such as EMKEY, have been applied to promote cognition in people with some type of cognitive or motor disabilities [47].…”
Section: Summary Resultsmentioning
confidence: 77%
“…This function is extremely important because if we transfer the emulator to real computing environments, such as work or education, the person with motor disabilities must be able to correctly drag objects using EMKEY. This statement is related to previous research in which technological devices, such as EMKEY, have been applied to promote cognition in people with some type of cognitive or motor disabilities [47].…”
Section: Summary Resultsmentioning
confidence: 77%
“…Previous studies have indicated that computers and the Internet have been able to meet the new requirements of the great developments in the field of population growth, information, technology, communication, and education (Alkhawaldeh, Hyassat, Al-Zboon & Ahmad, 2017). The most important advantages provided by the computer and the Internet are the development of the means of communication, raising its efficiency, speed, and high accuracy, providing information and raising the level of the information product, facilitating human communication processes in societies where the communication technology using the Internet has many characteristics, including interactivity, mobility, prevalence and spread (Adam & Tatnall, 2017;Benmarrakchi, Elhammoumi & Jamal, 2019;Ramos-Galarza et al, 2020). Further, the content of any other media has become available in other media, and this leads to the disappearance of the differences between the means of mass communication, as well as providing wider learning opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%